2008
DOI: 10.1177/1753193407087892
|View full text |Cite
|
Sign up to set email alerts
|

Neurolysis of the Distal Superficial Radial Nerve for Dysaesthesia Due to Nerve Tethering

Abstract: The subcutaneous course of the superficial radial nerve over the radial border of the wrist and hand renders it very susceptible to injury. Both traumatic and iatrogenic injury can produce tethering of this nerve, presenting as dysaesthesia. This study was designed to evaluate the efficacy of neurolysis of the distal superficial radial nerve for this condition. Twenty-five cases of tethered superficial radial nerves underwent neurolysis. At final follow-up (mean 3.5 years), fourteen cases reported symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
1
11
0
4
Order By: Relevance
“…12 Deep palpation in the uninjured wrist can elicit pain, so the examiner should compare responses to bilateral examination, but radial sensory nerve findings can usually be distinguished from scaphoid pain. 13 The anatomical snuffbox is the groove between the tendons of the extensor pollicis longus on the ulnar side and the extensor pollicis brevis and abductor pollicis longus on the radial side. Alternatively, pain with digital pressure over the scaphoid tubercle may indicate scaphoid fracture.…”
mentioning
confidence: 99%
“…12 Deep palpation in the uninjured wrist can elicit pain, so the examiner should compare responses to bilateral examination, but radial sensory nerve findings can usually be distinguished from scaphoid pain. 13 The anatomical snuffbox is the groove between the tendons of the extensor pollicis longus on the ulnar side and the extensor pollicis brevis and abductor pollicis longus on the radial side. Alternatively, pain with digital pressure over the scaphoid tubercle may indicate scaphoid fracture.…”
mentioning
confidence: 99%
“…The superficial radial nerve is susceptible to neural disorder due to its anatomical location . While it is well known that neuroma formation causes symptoms such as radiating pain, neural adhesion against surrounding scar tissue can elicit pain as well . The pathophysiology of neural adhesion is characterized by not only mechanical stress due to scar tissue and the ischemic condition of the nerves, but also by nerve traction caused by loss of smooth gliding during neighboring joint motion.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive diagnostic criteria for neural adhesion have not yet been established and thus diagnosis might be difficult clinically. Some surgeons have reported that recurrent adhesion after neurolysis is not uncommon, but great care should be taken in operations for neurolysis because of the unreliable outcomes …”
mentioning
confidence: 99%
See 2 more Smart Citations